Implementasi Teori Belajar Konstruktivisme dalam Pembentukan Karakter Anak di Lembaga Pendidikan Islam - Wardati, Laila; S, Khotimatul Majidah; Yusri, Dairina (Sekolah Tinggi Agama Islam Sumatera Medan, 2024)
The importance of character building from an early age requires a special theory in formal education. This research analyses the implementation of Social Constructivism Learning Theory in children's character building in Islamic educational institutions, focusing on its implementation and significance. This research uses a qualitative method with a descriptive approach. Data collection used observation, interviews and documentation studies. The research informants were teachers and students. data analysis through the stages of data collection, data reduction, data presentation and conclusion drawing. The findings show that this theory emphasises the importance of children's interaction with the environment, such as teachers and peers, to internalise character values. At Raudhatul Athfal Nur Azro, learning uses methods such as games, cooking class, storytelling, sociodrama, and positive behaviour modelling. The concept of zone of proximal development is applied to help children understand the concept of character through direct experience. Overall, the use of this theory is crucial in shaping positive character in early childhood, creating a generation with integrity and empathy. This research contributes to providing a strong foundation for positive character development in the early stages of children's lives, creating a generation with integrity and empathy, ready to face the complex moral demands of society.